Relationship between changing swimming direction and 25 m speed swimming in competitive university swimmers - Noguchi, T.; Demura, S.; Sato, S.; Nakada, M.; Kitabayashi, T.; Osugi, T. (Japanese Journal of Sciences in Swimming and Water Exercise, 2004)
This study aimed to examine a relationship between changing swimming direction and 25 m speed swimming. The changing swimming direction test was selected to measure coordination ability in water, and the 25 m speed swimming test to measure speed ability. The subjects were 36 competitive university swimmers including six water polo players. In both tests, they started by kicking the wall in the water. The intra-class correlation (ICC) between two trials was calculated to examine reliability. Pearson' s correlation coefficient was used to examine the relationship between both tests. Reliability in both tests was judged to be very high, because their ICCs were 0.98. Although both tests showed a significant, moderate correlation (r = 0.54), it was judged that their relationship is not very high because of a low degree of inter-contribution (under 30%). Factors other than swimming speed are considered to relate to the changing swimming direction test selected in this study. It is suggested that water polo players are excellent in changing swimming direction.